Isolasi bakteri probiotik Lactobacillus sp dari usus ikan mas (Cyprinus carpio) - Novitarizky, Intan A.; Manoppo, Henky; Longdong, Sammy N.J. (Universitas Sam Ratulangi, 2018)
The objective of research was to isolate the probiotic bacteria from intestine of carp. Isolation was performed by weighing 1 g of intestine, crushed and inserted in a reaction tube containing 9 mL of NaCl then centrifuged. Supernatant was taken and spread over the agar medium by scatter method. The bacteria-stocked medium was then incubated in an incubator at 28°C for 24-48 hours. The growing colonies were re-isolated on the agar medium to obtain pure colonies. The bacteria were then identified by morphological observation, resulting pigment and gram staining. Five nile tilapia (sized 8 – 10 cm) were used in pathogenicity test and placed in the aquarium. Fish were injected with 0.2 ml of Lactobacillus solution containing 1x107 CFU/mL via intraperitoneal injection. The results showed that the bacteria Lactobacillus sp had rod-shaped characteristics, white pigment and gram positive and not pathogenic, which means it can be used as probiotic for aquaculture.Keywords : Lactobacillus sp, carp, probiotic, pathogenicity test